NILAI BUDAYA DALAM SASTRA LISAN MANIAMAS MASYARAKAT DAYAK BEKATI PALAYO KABUPATEN BENGKAYANG - Sitompul, Novriska Nelda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The background of this research is to describe the cultural values in the Maniamas oral literature of the Dayak Bekati Palayo community, Bengkayang Regency. This study focuses on the problem of examining how cultural values reflect the relationship between humans and God in Maniamas oral literature?, how cultural values reflect human relationships with oneself in Maniamas oral literature? ?, how are the cultural values that reflect the relationship between humans and nature in Maniamas oral literature?, how is the implementation of Maniamas oral literature in Indonesian lessons in the 2013 curriculum?. The research method used in this research is descriptive qualitative method. The approach used in this research is a sociological approach. Data collection techniques in this study are interview techniques and recording techniques. The results of this study (1) the cultural value of human relations with God, namely believing in ghosts and believing in supernatural things. (2) the cultural value of human relations with oneself, namely emotion, strong will, honesty, responsibility, and patience (3) the cultural value of human-human relations, namely being obedient to parents. (4) the cultural value of human relations with nature, namely humans need nature and human marriages with heavenly beings. (5) a plan for implementing the results of this research has been drawn up in learning Indonesian in high school.